PERAN PEMASARAN DIGITAL DAN BRANDING DALAM MEMPENGARUHI MINAT BELI MELALUI KESADARAN MEREK SEBAGAI INTERVENING - Ferry Agsta Pramudya; Ambar Lukitaningsih; Putri Dwi Cahyani (Jurnal Ekonomi dan Bisnis Indonesia, 2025)
This study aims to analyze the role of digital marketing and branding in influencing purchase intention with brand awareness as an intervening variable among Starcross consumers in Yogyakarta. This research employs a quantitative method using primary data collected through a Likert-scale questionnaire. The sample consists of 105 respondents who are Starcross consumers, selected using purposive sampling technique. Data analysis was conducted using multiple linear regression and Sobel test with the assistance of SPSS software. The results indicate that digital marketing and branding have a positive and significant effect on brand awareness. Furthermore, digital marketing, branding, and brand awareness also have a positive and significant influence on purchase intention. The mediation test results reveal that brand awareness effectively mediates the relationship between digital marketing and branding toward purchase intention. These findings highlight the importance of integrating digital marketing and branding strategies to enhance brand awareness and stimulate consumers’ purchase intention, particularly in the local fashion industry.